2009
DOI: 10.11650/twjm/1500405355
|View full text |Cite
|
Sign up to set email alerts
|

On Global Solutions and Blow-Up of Solutions for a Nonlinearly Damped Petrovsky System

Abstract: We consider the initial boundary value problem for a Petrovsky system with nonlinear dampingin a bounded domain. We showed that the solution is global in time under some conditions without the relation between m and p. We also prove that the local solution blows-up in finite time if p > m and the initial energy is nonngeative. The decay estimates of the energy function and the estimates of the lifespan of solutions are given. In this way, we can extend the result of ([6]).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 5 publications
0
32
0
Order By: Relevance
“…Under some assumptions, he showed the solution of (1.9) decays exponentially if g behaves like a linear function, whereas the decay is polynomially otherwise. For more decay results, we refer the reader to [5,6,7,10,16,19,25,26,40,43,47,48] and the references therein. In recent years, more authors pay attention to the lower and upper bounds for blow-up time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under some assumptions, he showed the solution of (1.9) decays exponentially if g behaves like a linear function, whereas the decay is polynomially otherwise. For more decay results, we refer the reader to [5,6,7,10,16,19,25,26,40,43,47,48] and the references therein. In recent years, more authors pay attention to the lower and upper bounds for blow-up time.…”
Section: Introductionmentioning
confidence: 99%
“…The proof of global existence result is based on the potential well theory and the continuous principle; while for energy decay result, the proof is based on the Nakao's inequality and some techniques given in [43].…”
Section: Introductionmentioning
confidence: 99%
“…where a, b are defined as (12) and (13), respectively. For the case (iv), by the steps in case (i), we get (37) and (38) if and only if…”
Section: Proof Of Theorem 2 Letmentioning
confidence: 99%
“…In [10], Messaoudi studied problem (3) with g(u t ) = α |u t | p−1 u t and showed that the solution blows up in finite time if r > p and the energy is negative, while the solution is global if p ≥ r. Then Wu and Tsai in [12] showed that the solution is global under some conditions without any relation between p and r. They also proved the local solution blows up in finite time if r > p and the initial energy is nonnegative. In [9], Amroun and Benaissa proved the global existence of the solutions by means of the stable set method in H 2 0 (Ω ) combined with the Faedo-Galerkin procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Wu and Tsai [11] obtained global existence and blow up of the solution of the problem (1.2). Later, Chen and Zhou [2] studied blow up of the solution of the problem (1.2) for positive initial energy.…”
Section: Introductionmentioning
confidence: 99%